Association between alcohol consumption/alcohol use disorders and patient complexity: a cross-sectional study. Issue 8 (20th August 2020) - Sugiyama, Yoshifumi; Matsushima, Masato; Yoshimoto, Hisashi
Abstract : Objectives: The objective was to clarify the relationship between alcohol consumption/alcohol use disorders and patient complexity. Design: Cross-sectional study. Setting: A clinic located on a remote island in Okinawa, Japan, providing general outpatient practices and round-the-clock emergency services. Participants: Patients who lived on the island, visited Tarama Clinic from 1 April 2018 to 30 June 2018, were aged ≥20 years and had decision-making capacity were judged to be eligible for this study. Main outcome measures: Alcohol consumption/alcohol use disorders as measured by the Alcohol Use Disorders Identification Test (AUDIT) and patient complexity as scored by the Patient Centered Assessment Method (PCAM). Results: During the 3-month study period, 355 patients (163 women and 192 men) with mean (SD) age of 66.4 (13.6) years were included. Multiple regression analysis of PCAM scores showed that, after adjusting for age, sex, education, occupation, physical activity, smoking, annual medical expenses and number of family members living with the patient, AUDIT scores classified as 'dependence likely' were associated with PCAM scores (p value=0.040). Conclusions: Alcohol consumption and alcohol use disorders classified as dependence likely are associated with patient complexity.